Modelling water and sediment flow in branching channel system - Mohammed, Nashwan Kamal Al Deen (2017)
Operational problems associated with branching channels and water intakes increase over time due to localised sediment accumulations. The success of branching channel projects depends on the right design to increase the unit discharge and decrease the sediment concentration as much as possible. In addition, a branching channel from rivers and channels affects the bed morphology and causes erosion and sedimentation in the branching junction. There is still a lack of studies on the flow pattern in movable bed branching channel systems for different branching channel angles and bed widths to quantify the amount of water and sediment concentration in the branching channel and investigate its effect on the bed morphology. In this study, the hydraulic performance of differently angled branching channels was compared in an effort to maximise discharge, minimise sediment concentration and decrease its effect on the bed morphology. The objectives of the study are to investigate the effect of the branching angle and the bed width ratio on the water and sediment flow in the branching channel and scour hole characteristics (scour depth and scour length). The scour hole is formed in the main channel just downstream from the location of the branching channel entrance. This study also investigated the variation in velocity vertically and horizontally at the junction region and determined the total energy loss coefficient across the junction region. The objectives of the study were implemented experimentally using a physical model of 30, 45, 60, 75 and 90° branching channel angles with the main flow direction. In addition, three bed width ratios (30, 40 and 50%) and five total discharges (7.25, 8.5, 9.75, 11, and 12.25 L/s) were investigated for each branching angle scenario. A sand bed with d50 of 0.4 mm was used for all the experiments. In order to ensure sediment movement in the main channel at the upstream and to quantify the branching channel sediment concentration, a live-bed condition with flow intensity (Vu/Vc) of 1.1–1.5 was maintained in all experiments. The results indicated that branching angles of 30° and 45° increased the relative discharge ratios (QR) by approximately 5–10% compared with the discharge ratio for the 90° branching angle. The results also indicated that the branching channel sediment concentration and scour depth decreased as the branching channel angle decreased. The branching angles of 30° and 45° reduced the sediment concentrations by an average of 64% and 37%, respectively, compared with the concentration for the 90° branching angle. With respect to scour depth, the branching angle of 30° reduced the scour depth by approximately 14.4-46.7% compared with the scour depth for the 90° branching angle. The main reasons for forming the scour hole are the vortexes generated due to diverting some of the flow towards the branching channel and the downstream branching channel entrance sharp edge. The 30° branching angle recorded the smaller low velocity region at the beginning of the upstream side wall of the branching channel than other branching angles. Moreover, the velocity distribution in this branching angle is more uniform along the branching channel width than others. The outcomes from this study indicate that a branching angle of 30°– 45° is the best arrangement to increase the branching channel discharge, decrease the branching channel sediment concentration and decrease the scour depth at the junction region. Reducing the amount of branching channel sediment maintains the project efficiency of those depending on the branching channel flow. In addition, a high water unit discharge means a lower initial construction cost for the channel. Moreover, decreasing the scour depth helps to reduce the risks of a scouring effect on the side bank of the main channel or any nearby structures.